2015
DOI: 10.1111/joim.12447
|View full text |Cite
|
Sign up to set email alerts
|

Durable efficacy of liraglutide in patients with type 2 diabetes and pronounced insulin‐associated weight gain: 52‐week results from the Effect of Liraglutide on insulin‐associated wEight GAiN in patients with Type 2 diabetes' (ELEGANT) randomized controlled trial

Abstract: In T2DM patients with pronounced insulin-associated weight gain, addition of liraglutide within 2 years leads to sustained reversal of body weight, improved glycaemic control and decrease in insulin dose. Thus, liraglutide offers a valuable therapeutic option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Although treatment with liraglutide is expensive relative to other oral anti-diabetic drugs and reimbursement is limited in many healthcare systems, including Thailand, its use when other treatments fail or lead to significant side-effects may be suitable. Other studies21,22 have shown that liraglutide reverses pronounced insulin-associated weight gain, decreases insulin requirements, and improves glycemic control in T2DM patients. Such benefits may also result in additional cost savings, which are not included in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Although treatment with liraglutide is expensive relative to other oral anti-diabetic drugs and reimbursement is limited in many healthcare systems, including Thailand, its use when other treatments fail or lead to significant side-effects may be suitable. Other studies21,22 have shown that liraglutide reverses pronounced insulin-associated weight gain, decreases insulin requirements, and improves glycemic control in T2DM patients. Such benefits may also result in additional cost savings, which are not included in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…The frequency of hypoglycaemia was similar for both treatments, but gastrointestinal AEs were more common with liraglutide. A 52-week extension study of ELEGANT showed that the improvements in HbA 1c and body weight seen in the core study were sustained in the long term (Table 1) [44]. In a separate study of Japanese participants with Type 2 diabetes, 36 weeks of treatment with liraglutide added to an insulin regimen resulted in a significantly (P < 0.0001) greater reduction in HbA 1c than placebo and weight loss rather than weight gain [45].…”
Section: Treatment Intensification Of Basal Insulin With Glp-1rasmentioning
confidence: 97%
“…Twenty one studies with 7,437 participants (liraglutide group 4,509; placebo group 2,928) reported WC changes from the baseline [10][11][12][13][16][17][18]20,21,25,[27][28][29][30][32][33][34][36][37][38][39]. The WC was significantly reduced in the liraglutide group compared with the placebo group (MD −3.11 cm; 95% CI, −3.59 to −2.62) (Fig.…”
Section: Article In Pressmentioning
confidence: 99%